AB0320 BDMARDS SURVIVAL: THE TUNISIAN DATA. (2nd June 2020) - Saadaoui, K.; Sahli, H.; Boussaid, S.; Jemmali, S.; Rekik, S.; Cheour, E.; Elleuch, M.
Abstract : Background: The advent of biotherapies in the late 90s radically changed the face of inflammatory diseases including rheumatoid arthritis. The survival of these innovative therapies is an indicator, in clinical practice, of their long-term efficacy and safety. Objectives: The objective of this study was to assess their use in Tunisia through their survival during rheumatoid arthritis as well as to determine the factors that may influence their therapeutic maintenance in real life. Methods: This is a retrospective study including RA patients (ACR/EULAR 2010 criteria) and putted on biotherapy between 01-01-2014 and 12-31-2016. They were followed until 12-31-2018. The therapeutic maintenance rate at 12, 24, 36 and 48 months as well as the survival curves of biotherapies were analyzed using the Kaplan-Meier survival curves and compared by the Log-rank test. Reasons for interruption and patterns of biological change have been reported. Finally, an analysis of factors influencing survival was performed using Cox regression. A p<0.05 was considered statistically significant. Results: Three hundred seventy-four patients were included in the study; sex ratio was 0, 147. The baseline age was 55 ± 12.5 years [20 – 90] and the average disease duration was 11.7 ± 6.7 years [2 – 41]. Rheumatoid factor and ACPA were positive respectively in 79% and 71% cases. After failure of cDMARD, the first biotherapy prescribed was etanercept in 54% of cases, adalimumab in 14% of cases, certolizumab pegol 13%, infliximab 6%, tocilizumab 6% and rituximab in 7% of cases, with an average DAS28 at baseline 6.01 ± 0.89 [5, 37 – 6, 50]. Association with methotrexate was observed in 59, 6% case and with corticosteroid in 57.2% case. Drug persistency rate at 12 months was 85.8%; at 24 months, 69.9%; at 36 months, 60.6% and at 48 months, 55.9%. Survival was on average 41.7 months with 95% CI (39.47 - 43.91). The presence of rheumatoid factors, the co-prescription of methotrexate as well as good initial therapeutic response were predictor of a better survival of biologicals at a statistically significant level p<0.01 (Hazard Ratios for pursuit of biotherapy were respectively 1.79, 1.91 and 2, 3). The use of glucocorticoids was a negative predictor of retention (Hazard Ratio for therapy pursuit was 0.47 p < 0.001). This first biotherapy was stopped in 39% of cases and ineffectiveness was the major reason of interruption (52.7%). The anti-TNFα cycling was the most adopted therapeutic strategy with 64.6% of cases. The survival rates of the second biotherapy at 12, 24 and 36 months were 91%, 76.4% and 72.1%, respectively. Conclusion: Our study provides information about biotherapy prescription practices in Tunisia and their effectiveness in "real life". It informs us about the use of these new therapies in our country and has shown an efficacy and a tolerance profile close to those reported in international registers. Disclosure of Interests: None declared